Cellular Epigenetic Targets and Epidrugs in Breast Cancer Therapy: Mechanisms, Challenges, and Future Perspectives - Ibrahim S. Alalhareth; Saleh M. Alyami; Ali H. Alshareef; Ahmed O. Ajeibi; Manea F. Al Munjem; Ahmad A. Elfifi; Meshal M. Alsharif; Seham A. Alzahrani; Mohammed A. Alqaad; Marwa B. Bakir; Basel A. Abdel-Wahab (Pharmaceuticals)
Breast cancer is the most common malignancy affecting women, manifesting as a heterogeneous disease with diverse molecular characteristics and clinical presentations. Recent studies have elucidated the role of epigenetic modifications in the pathogenesis of breast cancer, including drug resistance and efflux characteristics, offering potential new diagnostic and prognostic markers, treatment efficacy predictors, and therapeutic agents. Key modifications include DNA cytosine methylation and the covalent modification of histone proteins. Unlike genetic mutations, reprogramming the epigenetic landscape of the cancer epigenome is a promising targeted therapy for the treatment and reversal of drug resistance. Epidrugs, which target DNA methylation and histone modifications, can provide novel options for the treatment of breast cancer by reversing the acquired resistance to treatment. Currently, the most promising approach involves combination therapies consisting of epidrugs with immune checkpoint inhibitors. This review examines the aberrant epigenetic regulation of breast cancer initiation and progression, focusing on modifications related to estrogen signaling, drug resistance, cancer progression, and the epithelial–mesenchymal transition (EMT). It examines existing epigenetic drugs for treating breast cancer, including agents that modify DNA, inhibitors of histone acetyltransferases, histone deacetylases, histone methyltransferases, and histone demethyltransferases. It also delves into ongoing studies on combining epidrugs with other therapies and addresses the upcoming obstacles in this field.